Ion channel mechanisms of rat tail artery contraction-relaxation by menthol involving, respectively, TRPM8 activation and L-type Ca2+ channel inhibition - Melanaphy, D; Johnson, C; Kustov, M; Watson, C; Borysova, L; Burdyga, T; Zholos, A (American Physiological Society, 2016)
Transient receptor potential melastatin 8 (TRPM8) is the principal cold and menthol receptor channel. Characterized primarily for its cold-sensing role in sensory neurons, it is expressed and functional in several nonneuronal tissues, including vasculature. We previously demonstrated that menthol causes variable mechanical responses (vasoconstriction, vasodilatation, or biphasic reactions) in isolated arteries, depending on vascular tone. Here we aimed to dissect the specific ion channel mechanisms and corresponding Ca2+ signaling pathways underlying such complex responses to menthol and other TRPM8 ligands in rat tail artery myocytes using patch-clamp electrophysiology, confocal Ca2+ imaging, and ratiometric Ca2+ recording. Menthol (300 μM, a concentration typically used to induce TRPM8 currents) strongly inhibited L-type Ca2+ channel current (L-ICa) in isolated myocytes, especially its sustained component, most relevant for depolarization-induced vasoconstriction. In contraction studies, with nifedipine present (10 μM) to abolish L-ICa contribution to phenylephrine (PE)-induced vasoconstrictions of vascular rings, a marked increase in tone was observed with menthol, similar to resting (i.e., without α-adrenoceptor stimulation by PE) conditions, when L-type channels were mostly deactivated. Menthol-induced increases in PE-induced vasoconstrictions could be inhibited both by the TRPM8 antagonist AMTB (thus confirming the specific role of TRPM8) and by cyclopiazonic acid treatment to deplete Ca2+ stores, pointing to a major contribution of Ca2+ release from the sarcoplasmic reticulum in these contractile responses. Immunocytochemical analysis has indeed revealed colocalization of TRPM8 and InsP3 receptors. Moreover, menthol Ca2+ responses, which were somewhat reduced under Ca2+-free conditions, were strongly reduced by cyclopiazonic acid treatment to deplete Ca2+ store, whereas caffeine-induced Ca2+ responses were blunted in the presence of menthol. Finally, two other common TRPM8 agonists, WS-12 and icilin, also inhibited L-ICa With respect to L-ICa inhibition, WS-12 is the most selective agonist. It augmented PE-induced contractions, whereas any secondary phase of vasorelaxation (as with menthol) was completely lacking. Thus TRPM8 channels are functionally active in rat tail artery myocytes and play a distinct direct stimulatory role in control of vascular tone. However, indirect effects of TRPM8 agonists, which are unrelated to TRPM8, are mediated by inhibition of L-type Ca2+ channels and largely obscure TRPM8-mediated vasoconstriction. These findings will promote our understanding of the vascular TRPM8 role, especially the well-known hypotensive effect of menthol, and may also have certain translational implications (e.g., in cardiovascular surgery, organ storage, transplantation, and Raynaud's phenomenon).